CORRELATION BETWEEN THE DURATION OF ANTI-EPILEPTIC DRUGS THERAPY AND VITAMIN D LEVEL IN EPILEPTIC CHILDREN - Hadia Anggriani Machmoed; Nadya A R Bubakar; Urfianty Urfianty; Idham Jaya Ganda (International Journal of Health Science & Medical Research, 2023)
Long-term use of antiepileptic drugs (AEDs) for epilepsy causes a decrease in vitamin D levels due to the activation of liver cytochrome P450 enzymes. The novelty of this study is due to researching about correlation between the duration of anti-epileptic drugs therapy and vitamin d level in epileptic children This cross-sectional study was conducted from October - December 2021in children with epilepsy aged 1 month to 18 years admitted to pediatric neurology polyclinic of DR Wahidin Sudirohusodo. They were divided into two groups: epileptic children receiving AEDs treatment ≤ 1 year and epileptic children receiving AEDs treatment 1 year. Statistical analysis showed no significant relationship between the duration of AEDs use and the incidence of vitamin D deficiency in children with epilepsy.Keywords: Vitamin D Deficiency; Antiepileptic Drugs; Epilepsy